Cutting edge: TCR delta gene is frequently rearranged in adult B lymphocytes - Krejci, Ondrej; Prouzova, Zuzana; Horvath, Ondrej; Trka, Jan; Hrusak, Ondrej (Journal of immunology (Baltimore, Md., 2003)
TCR gene rearrangement generates diversity of T lymphocytes by V(D)J recombination. Ig genes are rearranged in B cells using the same enzyme machinery. Physiologically, TCR gene is postulated to rearrange exclusively in T lineage, but malignant B precursor lymphoblasts contain rearranged TCR genes in most patients. Several mechanisms by which malignant cells break the regulation of V(D)J recombination have been proposed. In this study we show that incomplete TCR delta rearrangements V2-D3 and D2-D3 occur each in up to 16% alleles in B lymphocytes of all healthy donors studied, but complete VDJ rearrangement was negative at the sensitivity limit of 1%. Data are based on real-time quantitative PCR validated by PAGE and sequencing of the cloned products. Therefore, TCR genes rearrange not exclusively in T lineage. This study opens up further questions regarding the exact extent of the "cross-lineage" TCR or Ig rearrangements in normal lymphocytes, specific subsets in which the cross-lineage rearrangements occur, and the physiological importance of these rearrangements.
Keywords: Gene Rearrangement, delta-Chain T-Cell Antigen Receptor; Humans; HeLa buňky; Tumor Cells, Cultured; buňky HT-29; Sequence Analysis, DNA; klonování DNA; podskupiny B-lymfocytů; genetické markery; dospělí; genová přestavba - delta řetězec receptoru antigenů T-buněk; HT29 Cells; hematopoetické kmenové buňky; lidé; B-Lymphocyte Subsets; nádorové buňky kultivované; sekvenční analýza DNA; Adult; Receptors, Antigen, T-Cell, gamma-delta; receptory antigenů T-buněk gama-delta; HeLa Cells; polymerázová řetězová reakce; Genetic Markers; Polymerase Chain Reaction; Hematopoietic Stem Cells; akutní lymfatická leukemie; Cloning, Molecular; Precursor Cell Lymphoblastic Leukemia-Lymphoma